The Effect of Human Resource Planning and Work Environment Mediated by Motivation on Employee Performance at PT Bumi Guna Fokusindo - Farien Dwi Putri; Hendratmoko Hendratmoko (Syntax Idea)
This study aims to evaluate PT Bumi Guna Fokusindo's efforts in improving employee performance through human resource (HR) planning, the work environment, and the mediating role of motivation. The issues raised focus on the effectiveness of HR planning and work environment conditions in influencing performance, and to what extent motivation acts as a mediator in the relationship between these variables. The study analyzes the impact of HR planning and the work environment on employee performance; the role of motivation in mediating the influence of HR planning and the work environment on performance; and the direct effect of motivation on employee performance. Primary data was collected through questionnaires and analyzed using the Partial Least Squares (PLS) technique with SmartPLS 4.0. The results show that HR planning has a positive and significant effect on employee performance, emphasizing the importance of effective HR planning. However, the work environment does not have a significant effect on employee performance, although it shows a positive direction. Motivation also does not show a significant influence. HR planning does not significantly affect employee motivation. On the other hand, the work environment has been proven to significantly increase motivation. However, when employee performance is mediated by motivation between HR planning and the work environment, its effect remains insignificant